Assessment strategy based on authentic assessment to identify high school students' ability in assessing drama texts and drama performances - Sukmana, Ece; Saeprokhman, Asep; Irawan, Dedi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Drama learning plays an important role in training students to sharpen their expressive abilities in performing arts. This study aims to develop and implement an authentic assessment-based assessment strategy to identify high school students' ability to assess drama texts and drama performances. The research method used is research and development (R&D) which involves several stages, namely needs analysis, instrument design, and assessment model development. The R&D model used in this research is the ADDIE model (Analysis-Design-Develop-Implement-Evaluate). The results showed that the developed authentic assessment model can improve students' ability to assess drama texts and performances. Teachers who use this model find it helpful in developing more effective and comprehensive assessment instruments. In addition, students showed improvement in critical thinking and evaluation skills, as well as the ability to identify and assess important elements in drama and performance texts. This study suggests that the implementation of authentic assessment strategies can make a positive contribution towards improving the quality of assessment in a secondary school setting.